2020
DOI: 10.1007/s10620-020-06228-z
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Workflows Improve Colonoscopy Follow-Up After Abnormal Fecal Immunochemical Tests in a Safety-Net System

Abstract: Background How clinical teams function varies across sites and may affect follow-up of abnormal fecal immunochemical test (FIT) results. Aims This study aimed to identify the characteristics of clinical practices associated with higher diagnostic colonoscopy completion after an abnormal FIT result in a multi-site integrated safety-net system. Methods We distributed survey questionnaires about tracking and follow-up of abnormal FIT results to primary care team members across 11 safety-net clinics from January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Katz et al found that fully staffed teams are able to reconfigure roles and responsibilities and potentially develop new workflow processes [37]. Issaka and colleagues reported that having at least two members, and mostly MAs and nurses, communicate abnormal results to patients resulted in higher diagnostic colonoscopy completion [38]. Results of our matrix analysis further support the importance of engaging support staff in communication results.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Katz et al found that fully staffed teams are able to reconfigure roles and responsibilities and potentially develop new workflow processes [37]. Issaka and colleagues reported that having at least two members, and mostly MAs and nurses, communicate abnormal results to patients resulted in higher diagnostic colonoscopy completion [38]. Results of our matrix analysis further support the importance of engaging support staff in communication results.…”
Section: Discussionsupporting
confidence: 59%
“…These findings on communication and interactions from MA's and nurses highlight the importance of team-based care in primary care. Studies have found a positive association between team-based care and strategies that promote patient engagement [37] and better health outcomes [38]. Katz et al found that fully staffed teams are able to reconfigure roles and responsibilities and potentially develop new workflow processes [37].…”
Section: Discussionmentioning
confidence: 99%
“…Create workflows to track patients with abnormal FIT results until colonoscopy is completed. 5 4. Increase gastroenterology staffing to accommodate the expected surge in procedural demand.…”
Section: Openmentioning
confidence: 99%
“…CRC screening may also involve annual stool blood tests, such as the FIT or gFOBT, and follow-up with diagnostic colonoscopy if needed for abnormal findings. Communication of abnormal FIT results are associated with improved adherence to follow-up colonoscopy [6].…”
Section: Colorectal Cancer Screening Recommendationsmentioning
confidence: 99%